Characterization of the hypothalamo–pituitary–gonadal axis in low and high egg producing turkey hens - Kristen Brady; Tom E. Porter; Hsiao-Ching Liu; Julie A. Long (Poultry Science, 2020)
ABSTRACT: Variation in egg production exists in commercial turkey hens, with low egg producing hens (LEPH) costing more per egg produced than high egg producing hens (HEPH). Egg production correlates with ovulation frequency, which is governed by the hypothalamic–pituitary–gonadal (HPG) axis. Ovulation is stimulated by a preovulatory surge (PS) of progesterone and luteinizing hormone, triggered by gonadotropin releasing hormone release and inhibited by gonadotropin inhibiting hormone. Differences between LEPH and HEPH were characterized by determining HPG axis plasma hormone profiles and mRNA levels for key genes, both outside and inside of the PS (n = 3 per group). Data were analyzed with a 2-way ANOVA using the mixed models procedure of SAS. In the HPG axis, plasma progesterone levels were not affected by egg production level but were elevated during the PS. In contrast, plasma estradiol levels were higher in HEPH than in LEPH but were not associated with the PS. LEPH exhibited decreased gene expression associated with ovulation stimulation and increased gene expression associated with ovulation inhibition in the hypothalamus and pituitary. In ovarian follicle cells, LEPH displayed decreased gene expression associated with progesterone, androgen, and estradiol production in the F1 follicle granulosa cells, F5 theca interna cells, and small white follicle cells, respectively. Different degrees of stimulation and inhibition within all tissues of the HPG axis were noted between LEPH and HEPH turkey hens, with HEPH showing higher expression of genes related to ovulation and steroidogenesis.